Knowledge, Attitude, Oral Hygiene Practice and Self-Perception on Periodontal Health among Older Adult Population in Malaysia - Edwin Thomas, Annabel Shanta; Taib, Haslina; Berahim, Zurairah; Zainuddin, Siti Lailatul Akmar; Mohd Adnan, Munirah (UI Scholars Hub, 2024)
Objective: This study aimed to assess the knowledge, attitude, oral hygiene practice, and self-perception of periodontal health among the older adult population in Malaysia and its association with demographic factors. Methods: An online questionnaire assessing their knowledge, attitude, oral hygiene practices, and self-perception of periodontal disease was distributed to adults aged 50 years and above. Results: 397 respondents participated. The mean knowledge score was 1.36 (SD 0.92), significantly associated with gender, ethnicity, education, and occupation. About 63% of respondents know that poor oral hygiene is related to general health and is significantly associated with ethnicity (p = 0.016) and occupation (p = 0.009). Most respondents showed good oral hygiene practice but visited the dentist only when necessary (45%). Many of them have positive perceptions of their gum health status (81.6%) and are significantly associated with ethnicity (p = 0.007), education level, and occupations. Conclusion: This study showed inadequate knowledge about periodontal health among older adults. The attitude, practices, and self-perception of periodontal disease are mainly associated with ethnicity, educational levels, and occupations. Awareness of periodontal disease should be reinforced among older adults for better quality of life.